Authority and Performance Sociological Perspectives on the Council of Chalcedon (AD 451) - Amirav, Hagit (Hypomnemata, 2015)
One can hardly exaggerate the importance of the church councils in the 5th and 6th centuries. They provide us with great insights into the situation in the late Roman Empire and particularly into the role of the Church at that time. Because of the rich source materials, the dramatic course it took and its overall historical relevance, the Council of Chalcedon (AD 451) is one of the most important events of that period. The decrees of this council led to major upheavals in the Church which continue to this very day. Hagit Amirav presents the first study on the social dynamics and various roles played by the stakeholders of this council, the power plays of the imperial representatives and the bishops, their actions and statements designed to further a consensus. At the centre of this analysis lies Marcian in his dual role as Emperor of the East Roman Empire as well as a central figure in the Church.